(untitled) (JURNAL ADMINISTRASI PUBLIK, 2018)
This study focuses attention on the Application of Civil State Apparatus Discipline in the Regional Personnel Training Board of Siau Tagulandang Biaro Regency. This study was conducted because the discipline of the state civil apparatus has not complied with the prevailing government regulation. This research is expected to be useful for the Government of Siau Tagulandang Biaro Regency, especially in the Office of the Regional Personnel Training Agency in an effort to apply the discipline. This research was conducted at the office of the Regional Human Resources Training Board of Siau Tagulandang Biaro Regency. As the selected informant is the head of the agency, Head of the sub-section of general and staffing, Head of field of mutation and promotion information, Head of appraisal performance appraisal and awards development, Head of discipline sub-division and awards together with 4 persons as staff. This research is conducted by in-depth interview and by way of direct observation on the implementation of disciplinary application of State civil apparatus. The results of this study indicate that in applying the discipline of state civil apparatus is firm but there are still employees who ignore the rules of discipline in effect proved that disciplinary violations still occur. Disciplinary behaviours that often occur in the Regional Human Resources Training Board of Siau Tagulandang Biaro Regency. The conclusion that the researcher got in this research is the regulation that has been made concerning discipline of civil servant not yet effective executed because weakness of supervision from leader, civil apparatus of State still not realize its obligation so violating prohibition. The researcher’s suggestion from this research is to be more assertive from the leadership of the discipline in the implementation of the discipline, the leader is more direct with all employees, so that the employees can really perform the task in accordance with their obligations and need to be conducted research to improve the effectiveness of the Application of Civil State Apparatus Discipline the imposition of strict discipline this affects the employee when the Employee performs. Likewise with employees in the BKDD to more understand and obey government regulations. Keywords: Implementation, Discipline, State Civil Apparatus.